Self-evaluation Report and Improvement Plan: analysis and mapping of training needs of the Apulian School. First steps of a documentation research - Perla, Loredana; Vinci, Viviana (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
The results of a collaborative research-training – UNIBA-Apulian USR (Regional Education Department), that had as main objective the identification of lines of development of the Apulian School through a mapping of evaluation documentations (Self-evaluation report and improvement plans) of schools of all levels (679 in total) – showed the urgent need to standardize the modeling and tools for self-evaluation and improvement of schools. At the end of the research, DidaSco group has launched a training program in 80 Apulian schools with the aim to plan a new and more effective Improvement plan. It is described a new model of the DidaSco Improvement Plan, actually being tested / implemented in Apulian schools.